Real-time DNA barcoding in a rainforest using nanopore sequencing: Opportunities for rapid biodiversity assessments and local capacity building - Pomerantz, Aaron (2018)
Background: Advancements in portable scientific instruments provide promising avenues to expedite field work in order to understand the diverse array of organisms that inhabit our planet. Here, we tested the feasibility for in situ molecular analyses of endemic fauna using a portable laboratory fitting within a single backpack in one of the world's most imperiled biodiversity hotspots, the Ecuadorian Chocó rainforest. We used portable equipment, including the MinION nanopore sequencer (Oxford Nanopore Technologies) and the miniPCR (miniPCR), to perform DNA extraction, polymerase chain reaction amplification, and real-time DNA barcoding of reptile specimens in the field. Findings: We demonstrate that nanopore sequencing can be implemented in a remote tropical forest to quickly and accurately identify species using DNA barcoding, as we generated consensus sequences for species resolution with an accuracy of > 99% in less than 24 hours after collecting specimens. The flexibility of our mobile laboratory further allowed us to generate sequence information at the Universidad Tecnológica Indoamérica in Quito for rare, endangered, and undescribed species. This includes the recently rediscovered Jambato toad, which was thought to be extinct for 28 years. Sequences generated on the MinION required as few as 30 reads to achieve high accuracy relative to Sanger sequencing, and with further multiplexing of samples, nanopore sequencing can become a cost-effective approach for rapid and portable DNA barcoding. Conclusions: Overall, we establish how mobile laboratories and nanopore sequencing can help to accelerate species identification in remote areas to aid in conservation efforts and be applied to research facilities in developing countries. This opens up possibilities for biodiversity studies by promoting local research capacity building, teaching nonspecialists and students about the environment, tackling wildlife crime, and promoting conservation via research-focused ecotourism. © The Author(s) 2018.